2020
DOI: 10.1002/ange.201916651
|View full text |Cite
|
Sign up to set email alerts
|

Trishomoaromatic (B3N3Ph6) Dianion: Characterization and Two‐Electron Reduction

Abstract: Benzene, a common aromatic compound, can be converted into an unstable antiaromatic 8π‐electron intermediate through two‐electron reduction. However, as an isoelectronic equivalent of benzene, borazine (B3N3Ph6), having weak aromaticity, undergoes a totally different two‐electron reduction to afford (B3N3R6)2− homoaromatic compounds. Reported here is the synthesis of homoaromatic (B3N3Ph6)2− by the reduction of B3N3Ph6 with either potassium or rubidium in the presence of 18‐crown‐6 ether. Theoretical investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…However, to the best our knowledge, their reduction chemistry has been almost unexplored. Only very recently have Xi and co‐workers shown that reduction of Ph 6 B 3 N 3 six‐membered ring produced the corresponding trishomoaromatic dianion [14] . Recently, we reported the efficient synthesis of a series of BN‐naphthalene derivatives by a base‐promoted C−H borylation strategy [15] .…”
Section: Methodsmentioning
confidence: 99%
“…However, to the best our knowledge, their reduction chemistry has been almost unexplored. Only very recently have Xi and co‐workers shown that reduction of Ph 6 B 3 N 3 six‐membered ring produced the corresponding trishomoaromatic dianion [14] . Recently, we reported the efficient synthesis of a series of BN‐naphthalene derivatives by a base‐promoted C−H borylation strategy [15] .…”
Section: Methodsmentioning
confidence: 99%
“…Also, a number of heterocyclic derivatives of [C 6 R 6 ] 2− were prepared ( V – IX , Figure 1). [16–19] Due to their quinoid structure, V and VIII might be interpreted as the respective silicon‐ and boron‐substituted analogues of I – III . The other examples show structures which severely deviate from a planar ring as seen in the bicyclic diaza‐dipnictobicyclohexene VI , [20, 21] the tricyclic hexasilabenzene dianion VII [17] and the tetracyclic, trishomoaromatic species [B 3 N 3 Ph 6 ] 2− ( IX ) [19] .…”
Section: Introductionmentioning
confidence: 99%
“… [16–19] Due to their quinoid structure, V and VIII might be interpreted as the respective silicon‐ and boron‐substituted analogues of I – III . The other examples show structures which severely deviate from a planar ring as seen in the bicyclic diaza‐dipnictobicyclohexene VI , [20, 21] the tricyclic hexasilabenzene dianion VII [17] and the tetracyclic, trishomoaromatic species [B 3 N 3 Ph 6 ] 2− ( IX ) [19] . With the exception of VI and VII , all dianions shown in Figure 1 were prepared by two‐electron reduction of the respective neutral benzene derivative.…”
Section: Introductionmentioning
confidence: 99%